Technological mercantilism and technological colonization: new challenges for Russia - A. N. Petrov (Èkonomika Nauki, 2019)
An assessment is made of the prospects for Russia’s perception of advanced technological knowledge borrowed in industrialized countries for technological modernization of enterprises in the real sector of the economy. A review of the episodes of 2017–2019, which suggest that the policy of technological mercantelism is becoming more and more distinct and rigid forms, is presented. Especially frankly, it manifests itself in the example of relations between the USA and China, the USA and Russia.The history of the formation and evolution of technological protectionism, starting from the seventeenth century, is considered to the present day. It has been suggested that technological colonization, which is carried out by the technology-leading countries with respect to the countries of the technological periphery, is the highest evolutionary form of technological protectionism.